KEPEMIMPINAN DALAM MANAJEMEN PROYEK - Ida Bagus Gde Manuaba (Jurnal Anala, 2015)
The successful of the project doesnâ€™t depend on defining of fund only, but it also the available of some equipments, the material and the work method. The most important thing is the organizing, especially it the leadership. The leader should be able to manage his worker in achieving his goal for succeeding the project.The paper is a library research. It uses the inductive approach, basically some leadership literatures are intersected each other which means that the method uses the content of analysis.The research result show that the good leader is always busy in achieving the organization goal. He gives a personal satisfaction to his staffs without sacrificing them. The popular Indonesia leadership comes from our godfather of education (Ki Hajar Dewantoro) said that : (i) ing ngarso sung tulodo, in the front The leader must be a precedent, (ii) ing madyo mangun karso, at the middle, the leader must increase their staffâ€™ spirit and tekad, and (iii) tut wuri handayani, at the back the leader must push their staff in other to be dare and responsible.Â